Drawn to the word : the Bible and graphic design - Dillon, Amanda (Bible and its reception, 2021)
"A unique study of lectionaries and graphic design as a site of biblical reception How artists portrayed the Bible in large canvas paintings is frequently the subject of scholarly exploration, yet the presentation of biblical texts in contemporary graphic designs has been largely ignored. In this book Amanda Dillon engages multimodal analysis, a method of semiotic discourse, to explore how visual composition, texture, color, directionality, framing, angle, representations, and interactions produce potential meanings for biblical graphic designs. Dillon focuses on the artworks of two American graphic designers--the woodcuts designed by Meinrad Craighead for the Roman Catholic Sunday Missal and Nicholas Markell's illustrations for the worship books of the Evangelical Lutheran Church in America--to present the merits of multimodal analysis for biblical reception history."--Publisher